MEDIA MATH SCRABBLE UNTUK KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR: STUDI KUASI EKSPERIMENTAL - Anggraini, Vivi Sintiyah; Fanani, Achmad; Juniarso, Triman (Journal of the Indonesian Mathematics Education Society, 2019)
This research is based on the demands of the 21st century, one of which is the ability to think critically. But the reality is still relatively low, especially in mathematics so needed for means to deliver messages to achieve effective and efficient learning goals using innovative learning media there is math scrabble. The purpose of this study was to determine the effect of math scrabble media on critical thinking skills mathematics learning in class V at SDN Sedati Gede II Sidoarjo. It is a quantitative research, a quasi experimental design with a posttest only control design. The subjects were fifth grade students of SDN Sedati Gede II Sidoarjo, VA classes totaling 41 students as an experimental class and VB classes totaling 41 students as a control class. The data collection technique uses test instruments which are then tested using the t test. Based on the results of data analysis at a significance level of 5%, it is obtained the price of tcount 7> ttable 1.99, it can be concluded that there is the influence of math scrabble media on critical thinking skills mathematics learning in class V at SDN Sedati Gede II Sidoarjo. Keyword: critical thinking, mathematics, math scrabble.